Climate‐induced habitat suitability changes intensify fishing impacts on the life history of large yellow croaker (Larimichthys crocea). Issue 10 (1st October 2022) - Wang, Ya; Zhou, Xijie; Chen, Jiajie; Xie, Bin; Huang, Lingfeng
Abstract: Intense fishing pressure and climate change are major threats to the fish population and coastal fisheries. Larimichthys crocea (large yellow croaker) is a long‐lived fish, which performs seasonal migrations from its spawning and nursery grounds along the coast of the East China Sea (ECS) to overwintering grounds offshore. This study used length‐based analysis and habitat suitability index (HSI) model to evaluate the current life‐history parameters and overwintering habitat suitability of L. crocea, respectively. We compared recent (2019) and historical (1971–1982) life‐history parameters and overwintering HSI to analyze the fishing pressure and climate change effects on the overall population and overwintering phase of L. crocea . The length‐based analysis indicated serious overfishing of L. crocea, characterized by reduced catch, size truncation, constrained distribution, and advanced maturation causing a recruitment bottleneck. The overwintering HSI modeling results indicated that climate change has led to decreased sea surface temperature during L. crocea overwintering phase over the last half‐century, which in turn led to area decrease and an offshore‐oriented shifting of optimal overwintering habitat of L. crocea . The fishing‐caused size truncation may have constrained the migratory ability, and distribution of L. crocea subsequently led to the mismatch of the optimal overwintering habitat against climate change background, namely habitat bottleneck. Hence, while heavy fishing was the major cause of L. crocea collapse, climate‐induced overwintering habitat suitability may have intensified the fishery collapse of L. crocea population. It is important for management to consider both overfishing and climate change issues when developing stock enhancement activities and policy regulations, particularly for migratory long‐lived fish that share a similar life history to L. crocea . Combined with China's current restocking and stock enhancement initiatives, we propose recommendations for the future restocking of L. crocea in China. Abstract : Length‐based analysis indicated serious overfishing of Larimichthys crocea, characterized by reduced catch, size truncation, constrained distribution, and advanced maturation. The overwintering HSI modeling results indicated that climate change has led to decreased sea surface temperature during L. crocea overwintering phase, which in turn led to area decrease and an offshore‐oriented shifting of optimal overwintering habitat of L. crocea . Hence, heavily fishing was the major cause of L. crocea collapse, while climate‐induced overwintering habitat suitability may have intensified the fishery collapse of L. crocea population